Whey Utilisation: Sustainable Uses and Environmental Approach - Zandona, Elizabeta; Blažić, Marijana; Režek Jambrak, Anet (Food technology and biotechnology, 2021)
The dairy industry produces large amounts of whey as a by- or co-product, which has led to considerable environmental problems due to its high organic matter content. Over the past decades, possibilities of more environmentally and economically efficient whey utilisation have been studied, primarily to convert unwanted end products into a valuable raw material. Sustainable whey management is mostly oriented to biotechnological and food applications for the development of value-added products such as whey powders, whey proteins, functional food and beverages, edible films and coatings, lactic acid and other biochemicals, bioplastic, biofuels and similar valuable bioproducts. This paper provides an overview of the sustainable utilisation of whey and its constituents, considering new refining approaches and integrated processes to covert whey, or lactose and whey proteins to high value-added whey-based products.